Dose escalation for prostate stereotactic ablative radiotherapy (SABR): Late outcomes from two prospective clinical trials. Issue 2 (May 2018) - Alayed, Yasir; Cheung, Patrick; Pang, Geordi; Mamedov, Alexandre; D'Alimonte, Laura; Deabreu, Andrea; Commisso, Kristina; Commisso, Angela; Zhang, Liang; Quon, Harvey C.; Musunuru, Hima Bindu; Helou, Joelle; et al.
Abstract: Purpose: Optimal prostate SABR dose-fractionation is unknown. This study compares long-term outcomes from two prospective trials. Methods: Study1 patients had low-risk PCa and received 35 Gy/5. Study2 patients had low/intermediate-risk PCa and received 40 Gy/5. Biochemical failure (BF) was defined as nadir + 2. Results: 114 patients were included (study1, n = 84; study2, n = 30). Median follow-up was 9.6 years and 6.9 years. Median nPSA was 0.4 and 0.1 ng/ml. Nine patients had BF (8 in study1, 1 in study2); two were managed with ADT and four had local salvage. The BF rate was 2.5% and 12.8% at 5 and 10 years for study1 and 3.3% at 5 years for study 2. BF probability was 0% if PSA <0.4 at 4 years, and 20.5% at 10 years if PSA ≥0.4 ( p = 0.02). Nine patients died, none of PCa. No patient has metastases or castrate-resistance. At 10 years, OS and CSS were 90.4% ( p = 0.25) and 100%. Conclusions: Dose-escalated prostate SABR was associated with lower nPSAs but no difference in BF, OS, CSS or MFS. PSA <0.4 at 4 years was a predictor of biochemical control. Half of patients with BF were successfully salvaged. Given that this is a favorable-risk cohort, longer follow-up will be needed to see if the lower nPSA translates into lower BF rates.